2015
DOI: 10.1016/j.mayocp.2014.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Geomagnetic Activity With Implantable Cardioverter Defibrillator Shocks and Antitachycardia Pacing

Abstract: Objective Small-scale observational studies have suggested that geomagnetic activity (GMA) may negatively correlate with the frequency of life-threatening arrhythmias. We investigated a potential relationship between implantable cardioverter defibrillator (ICD) therapies and daily GMA recorded in a large database. Patients and Methods The ALTITUDE database, derived from the Boston Scientific LATITUDE remote monitoring system, was retrospectively analyzed for the frequency of ICD therapies. Daily GMA was expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
3
5
0
Order By: Relevance
“…However, none of these connections are present in the same form in all three solar storms. Such connection is consistent with the results published in [20,22], where the influence of the geomagnetic field was also identified and a connection with the geomagnetic parameters (Kp).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, none of these connections are present in the same form in all three solar storms. Such connection is consistent with the results published in [20,22], where the influence of the geomagnetic field was also identified and a connection with the geomagnetic parameters (Kp).…”
Section: Discussionsupporting
confidence: 92%
“…A similar study was conducted [19] and reached similar results. According to these studies, geomagnetic activity plays only a minor role in the cardiovascular mortality, a finding that has been confirmed in a study [20]. Strong solar storms affect the human circulatory system indirectly through the concentration of electric charges and also changes in the magnetic field in the terrestrial environment in which the monitored population lives [21].…”
Section: Introductionmentioning
confidence: 78%
“…If we extrapolate the Neutron action as it's accepted in radiotherapy [55] [56], we can presume that Neutron biological action is related with Neutrons are connecting with the H + anion (that is in high concentration in some lipid tissues and atheromatous plaques), converting to Protons, acting as damaging subject on cells and tissues, especially in damaged heart muscle, lipid infiltrated arterial walls, heart conduction system [54] [55]. The possible shield by the magnetic field from high Neutron activity in AMI and SCD was confirmed in a number of recent studies [28]- [30] and in a big international study of Mayo clinic (USA, Italy, Czech Republic [32]) that confirmed previous observations about inverse relationship of GMA with life threatening cardiac arrhythmia, [47] [54] and, also, at days of electrical hearts storms, when life threatening arrhythmias occurred three and more times daily (and also treated by implanted electrical defibrillators). The role of cosmic rays in physics and human life is widely discussed in recent publications [51] [57]- [59].…”
Section: Discussionmentioning
confidence: 93%
“…In many publications, it was shown that GMA storms were linked to a number of cardiovascular risk factors: arterial blood pressure, blood coagulation parameters, inflammation markers, some immunoglobulin fractions changes etc. and Cardiovascular Events (CVE) [6]- [26]; on the other hand, some important human pathology component's, like Sudden Cardiac Death (SCD)-one of the most frequent sorts of cardiac death for many years showed some "affinity" to low GMA [27]- [32]. Also Acute Myocardial Infarction (AMI) was in this group [27].…”
Section: Introductionmentioning
confidence: 89%
“…One of the challenges of applying physical activity monitor data to clinical outcomes is that there is no clear agreement on how best to model the high-density, time series data that is collected[ 7 10 ]. Specific to CIED data, investigators have applied broad summary statistics to these activity time series[ 11 13 ], although these methods, which shrink a yearly time series of information down to a single parameter, such as average or last value, lose large amounts of information. Other approaches have modeled data in the frequency domain, which can provide some additional information about long-term seasonality[ 14 ], but there remains no clear consensus on how best to model activity data.…”
Section: Introductionmentioning
confidence: 99%